Perubahan Paradigma Pengelolaan Organisasi: Studi Terhadap Kelompok Tari Nan Jombang Dance Company (NDJC) - Kabati Kabati (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Departs from the assumption that a paradigm shift will bring about changes in the social structure, goals, directions, actions, and social relationships that are built within an organization. The paradigm shift will also have an impact on the surrounding environment. This assumption was then developed by observing a dance group, Nan Jombang Dance Company (NJDC).